THE EFFECTIVENESS OF USING GOOGLE TRANSLATEON STUDENTS’ TRANSLATION AT MATHEMATIC FACULTY OF UNIVERSITAS NEGERI PADANG - Lestiana Zafitri; Eka Sustri Harida (Universitas Negeri Padang, 2017)
In this era of globalization in the form of communication between language translation still exist, and even tended increasingly important. Therefore, the technology provides it easily, including in translating. Due to technological developments, today there are various tools that can help to translate, for example google translate. Google translate does not need to be installed on your computer or laptop but the translator only need to connect to the Internet network. Thus translating into something which is foreign in the eyes of people who learn the language, because sometimes a lot of texts that are still using the original language from the international language, such as English that needs to be understood. From here, the students came the idea to understand the text by translating it by using the instant ways, that use relatively short time. One of them by using google translate. It shows the technology has been used to participate in the development process of translation in the students’ learning, it is for mathematic students in Universitas Negeri Padang. Google translate support over 100 languages at various levels. For some languages, google translate can pronounce translated text, highlight corresponding words and phrases in the source and target text, and act as a simple dictionary for single word input. If detect language is selected, text in an unknown language can be automatically identified. In this study, the researcher used survey research. The aim of the study is to investigate the information about the effectiveness of using google translate on students’ translation at mathematic faculty of Universitas Negeri Padang. To collect the data, the questionnaire of the effectiveness of google translate on students’ translation was distributed to the participant that consist of 40 students of mathematic faculty of Universitas Negeri Padang. The data gathered through the questionnaire was analyzed to investigate the effectiveness of google translate on students’ translation at mathematic faculty of Universitas Negeri Padang. Based on the result of the research, it can be concluded that google translation is effective to be used by the students in translating their books, articles, or tasks in order to understand their learning materials of the mathematic students. The students think that the google translation give a lot of benefits to help them to translate their task.